Zero-Base Budgeting: A Decision Package Manual (Book). - Smith, Sammie L.; Burns, Thomas J. (The Accounting Review, 1980)
Reviews the book "Zero-Base Budgeting: A Decision Package Manual," by L. Allan Austin and Logan M. Cheek.